Flow diversion of cerebral aneurysms - Park, Min S. (Min Sik), 1975-; Taussky, Philipp; Albuquerque, Felipe C.; McDougall, Cameron G. (Thieme, 2018)
From detachable balloons and GDC coils to the recent advent of flow diversion, practitioners of have endovascular neurosurgery been fortunate to work in an era of rapid and exciting advances. The first commercially available flow diverter in the U.S. was approved specifically for a small subset of cerebral aneurysms. Recent experience has demonstrated its utility in treating challenging or otherwise untreatable aneurysms, safely and efficaciously. The design of these devices requires learning radically different methods than those used in the deployment of other, non-braided stents. Flow Diver